SMART:SOLUTIONS FOR LOW ENTREPRENEURSHIP STUDENTS IN A DISRUPTION ERA - Siti Kamsiyati; Idam Ragil Widianto Atmojo (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
The purpose of this service is to improve the entrepreneurial spirit in the knowledge they pursue in the field of education. Subjects in this service were students of PGSD FKIP UNS. The method used in this service begins Workshop, Practice, Implementation. In the implementation of this training, the subject is asked to do the test, which is carried out before and after the implementation. Data analysis used using pretest and posttest analysis. The result of this activity was an increase in students' knowledge and understanding of entrepreneurship in the midst of disruption